2021
DOI: 10.1021/acs.chemmater.1c01969
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Void: Halogen Bonding and Aromatic Interactions to Program Luminescence and Electronic Properties of π-Conjugated Materials in the Solid State

Abstract: π-Conjugated materials are promising candidates for emerging organic optoelectronic devices empowered by molecular design. The unsolved challenges of predicting and controlling their packing as solids, central to their properties and performance, currently limits their practical application. As noncovalent interactions drive packing, control over such interactions are critical to bridging from chemical structure to functional properties. In molecular crystals, halogen bonding and interactions of aromatic rings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 209 publications
1
32
0
Order By: Relevance
“…Molecular switch 3 bearing a pentafluorophenyl group would be a suitable molecular design since its properties in the solid state has been widely studied. [18][19][20] The crystal structure of the unprotonated state of 3 (CCDC 2149789) was reported previously, 11 which existed in the E form in the crystal. In the previous study, we found that the addition of TFA (CF 3 COOH) altered the favoured conformer of 3 in the solution.…”
Section: Resultsmentioning
confidence: 83%
“…Molecular switch 3 bearing a pentafluorophenyl group would be a suitable molecular design since its properties in the solid state has been widely studied. [18][19][20] The crystal structure of the unprotonated state of 3 (CCDC 2149789) was reported previously, 11 which existed in the E form in the crystal. In the previous study, we found that the addition of TFA (CF 3 COOH) altered the favoured conformer of 3 in the solution.…”
Section: Resultsmentioning
confidence: 83%
“…[26,27] Homogeneous binary mixtures involving organic cocrystals and alloys can be considered to be highly miscible in which two constituent molecules are held together in a periodically arranged manner or in a randomly mixed fashion. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Binary organic cocrystals were commonly obtained by weak noncovalent interactions involving hydrogen bonding, [28][29][30][31] chargetransfer, [32][33][34][35][36][37] and halogen bonding interactions, [38,39] while alloys are constructed by substitution of structurally matched guest molecules at the host sites. [40][41][42][43][44][45] While binary heterostructures capable of producing well-defined micro-and nanoscale interfaces can be viewed as partially compatible combinations.…”
mentioning
confidence: 99%
“…Multi‐stimuli‐responsive RTP materials can be achieved by slight variations in the external environment owing to the weak intermolecular interactions of halogen bonding [15] . As shown in Figure 3a, the crystalline CBZCN/TPABr powder was found to respond sensitively to external mechanical grinding.…”
Section: Resultsmentioning
confidence: 99%
“…Halogen bonding formed between a halogen atom (Cl, Br, I) and a negative site (such as O, N, and S) is an effective tool in solid‐state supramolecular chemistry to stabilize the crystal structures [14] . The weak intermolecular halogen bonding may be disrupted through physical or chemical means, thus providing an effective approach to obtain multi‐stimuli‐responsive RTP materials [13, 15] . In addition, noncovalent intermolecular halogen bonding in the host–guest doped system is expected to construct highly efficient RTP materials [16] .…”
Section: Introductionmentioning
confidence: 99%